Ensuring uninterrupted supplies of antiretroviral drugs in resource-poor settings: an example from Malawi - Anthony D Harries; Erik J Schouten; Simon D Makombe; Edwin Libamba; Henry N Neufville; Eliab Some; Godfrey Kadewere; Douglas Lungu (Bulletin of the World Health Organization, 2007)
PROBLEM: Drug procurement and distribution practices are weak in many resource-poor countries, and are a major reason for lack of access to medicines. With many countries scaling up antiretroviral therapy (ART), it is vital to avoid interrupted drug supplies, which would lead to drug resistance and treatment failure. APPROACH: Malawi has adapted a model, based on that adopted by the country's Tuberculosis Control Programme, to allow rational ART drug forecasting. LOCAL SETTING: The model includes a focus on one standardized first-line ART regimen; a "push system" and "ceilings" for first-line ART drugs for facilities; use of starter pack and continuation pack kits; quarterly monitoring of patient outcomes and ART drug stocks at facility level; provision of a three-month buffer stock of ART drugs at facility level; and use of a procurement and distribution system outside central medical stores. LESSONS LEARNED: The focus on a single first-line regimen, "ceilings" for first-line ART drugs and quarterly data collections to calculate drug needs (for new and follow-up patients, respectively), as well as the use of an independent procurement facility, allow drug orders to be made 6-9 months ahead. These measures have so far ensured that there have been no ART drug stock-outs in the country.